Anaerobic membrane reactor: Biomethane from chicken manure and high-quality effluent. (January 2020) - Busato, Cynara Juliana; Da Ros, Cinzia; Pellay, Roberto; Barbierato, Paola; Pavan, Paolo
Abstract: Chicken manure was treated in a pilot scale reactor anaerobic membrane bioreactor constituted by a completely mixed reactor combined with an ultrafiltration tube-shaped membrane in a side-stream configuration. The process operated under mesophilic condition and the inhibition of high concentration of ammonia was avoided using an ammonia stripping system. The experimental plan included a preliminary evaluation, where organic loading rates between 1.0 and 7.6 kgVS/m3/day were tested. The organic load higher than 4 kgVS/m3/d caused the accumulation of volatile fatty acids and process instability. Application of the ammonia stripping was also evaluated. The best performances were achieved using a retention time of 21 days, an organic load between 1.4 and 2.0 kgVS/m3/d, and the recirculation of stripped permeate. Reduction of the ammonia permeate content by 90% through stripping and utilization of a mixture of chicken manure/water/permeate in a ratio of 0.22/0.72/0.72 w/w led to a specific biogas production of 0.59 m3biogas/kgVS and methane content of 66–69%. The ammonia thus removed can be recovered by sulphuric acid treatment as ammonium sulphate, which can be used as a fertilizer. The proposed configuration allowed satisfactory biogas production with appropriate methane percentages, recovery of ammonium sulphate, and a high-quality effluent. Highlights: Treatment of chicken manure under mesophilic condition in a single-stage mono-digestion configuration is feasible in AnMBR. Maximum specific gas production (0.59 m 3 biogas /kgVS) with 66–69% of methane was achieved recirculating stripped permeate. The highest performances were reached using a mix of chicken manure/permeate/water in a ratio of 0.22/0.72/0.72 w/w. Air stripping and sulphuric acid treatment led to 90% ammonium abatement.